Synthesis and Chemistry of 1,2,4,3-Triazaphosphole Derivatives - Ali, Tarik E.; Hassanin, Noha M.; Assiri, Mohammed A.; Abdel-Kariem, Somaia M. (Current Organic Chemistry, 2023)
This review describes the progress made during the last fifty years in the synthesis and chemistry of 1,2,4,3 triazaphospholes. This class of compounds has attracted tremendous homogeneous catalysis and interest in molecular materials science. These fascinating phosphorus heterocycles have conjugated π systems with high degrees of aromaticity. 1,2,4,3- Triazaphospholes can be designed through [3+2] cyclocondensation between functionalized hydrazines with phosphonoimidates that allow the incorporation of additional donor substituents into specific positions of the phosphorus heterocycle. In addition, [4+1] cyclocondensation between functionalized amidrazones and active phosphorus reagents is the most synthetically accessible method. The used strategies facilitated synthetic access to a completely new set of triazaphospholes leading to a much broader scope for potential applications. 1,2,4,3-triazaphospholes displayed reactivity towards a variety of reagents. The phosphorus is particularly prone to undergo oxidative 1,1-addition. Protic reagents such as alcohols, phenols, and amines can be added across the P=N bond of 2H-1,2,4,3-triazaphospholes to yield the dihydro-1,2,4,3-triazaphosphole derivatives. 1H- and 2H-1,2,4,3- triazaphospholes reacted with alcohols, ammonia and amines in the presence of sulfur or selenium to form dihydro- 1,2,4,3-triazaphosphole 3-chalcogenides. The appropriate difunctional reagents such as glycols, 2-azido alcohols and phenol with a heterodiene function in the ortho position reacted with 2H-1,2,4,3-triazaphospholes to yield products formed via 1,2-addition on P=N bond. Similar behavior is shown by 2-hydroxyacetophenone and 2- hydroxy-benzophenone. 2H-1,2,4,3-Triazaphospholes reacted with acetylenes to form [3+2] cycloadducts; the latter change to 1,2,3-diazaphospholes. [4+1] Cycloadditions occurred with α-diimines, azodicarboxylic esters, and 1,2-diketones; in the latter two cases, the resulting products dimerize.
Keywords: organophosphorus